Design, Synthesis and Pharmacological Evaluation of Noscapine Glycoconjugates. Issue 9 (4th March 2019) - Mishra, Kunj B; Tiwari, Neeraj; Bose, Priyanka; Singh, Rajan; Rawat, Arun K; Singh, Sumit K.; Mishra, Ram C.; Singh, Rakesh K; Tiwari, Vinod K.
Abstract: The present work is directed to design a series of molecules which are hybrids of two non‐toxic biocompatible chemical architectures, noscapine and carbohydrates. Fourteen, 7‐ O‐ noscapine analogues have been synthesized out of which one of the analogue is 7‐ O ‐propargylated derivative and others are in its glycoconjugate form with triazole bridging achieved via Click reaction, where dinuclear copper(I) thiodiacetate complex [(PPh3 )2 Cu(μ‐tda)Cu(PPh3 )2 ].6H2 O has been emerged as an excellent catalyst for the noscapine‐glyco Click‐coupling. All the developed noscapine glycoconjugates have been investigated for anticancer activity using HeLa cell line and anti‐leishmanial activity against Leishmania donovani . Result indicates that five of the developed noscapine glycoconjugates (5 a, 5 b, 5 c, 5 e and 5 l ) showed significant anti‐proliferative activity. On the other hand, four of them (5 b, 5 c, 5 e, and 5 l) showed significant anti‐leishmanial activity. Abstract : With an aid of highly efficient Click protocol, a series of 7‐ O‐ noscapine glycohybrids has been developed and evaluated for their anti‐cancer activity using HeLa cell line and anti‐leishmanial activity against Leishmania donovani . Result indicates that five of the developed noscapine glycoconjugates (5 a, 5 b, 5 c, 5 e, and 5 l) showed significant anti‐proliferative activity. On the other hand, four of the glycohybrids (5 b, 5 c, 5 e, and 5 l) displayed significant anti‐leishmanial activity.